Relationship between oxygen cost and C-reactive protein response to marathon running in college recreational runners - Takayama F; Aoyagi A; Takahashi K; Nabekura Y (Dove Medical Press, 2018)
Fuminori Takayama,1,2 Atsushi Aoyagi,3 Keigo Takahashi,2,3 Yoshiharu Nabekura1 1Faculty of Health and Sport Sciences, University of Tsukuba, Tsukuba-shi, Ibaraki, Japan; 2Japan Society for the Promotion of Science, Chiyoda-ku, Tokyo, Japan; 3Graduate School of Comprehensive Human Sciences, University of Tsukuba, Tsukuba-shi, Ibaraki, Japan Purpose: Individual variations in response of C-reactive protein (CRP) to acute strenuous exercise are less well known. The purpose of this study was to investigate the relationship between running economy and systemic inflammation following a marathon. Materials and methods: Sixteen college recreational runners participated in this study. To measure maximal oxygen uptake and running economy, the treadmill running test was performed 1–2 weeks before the marathon race. Running economy was defined as oxygen cost (mL/kg/km) at submaximal running. CRP and muscle damage markers (creatine kinase and lactate dehydrogenase) were measured before and 1, 2, and 3 days after the race. Results: All subjects completed the race in 4 hours 7 minutes 43 seconds±44 minute 29 seconds [mean±SD]. The marathon running significantly increased CRP and muscle damage markers. The levels of inflammation and muscle damage peaked after 1 day and remained high throughout the 3-day recovery period compared to that before the race. Spearman correlation analysis showed that the change in CRP level was significantly positively correlated with oxygen cost (r=0.619, P=0.011) but not maximal oxygen uptake. There was no significant relationship in responses between muscle damage markers and CRP. Conclusion: These findings suggest that running economy is related to postmarathon race CRP response. Further study to clarify the cause of the relationship and clinical significance of transient increase in CRP is necessary. Keywords: inflammation, oxygen consumption, C-reactive protein, muscle damage